2014
DOI: 10.1027/0227-5910/a000265
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Evaluated Suicide Prevention Programs Targeting Indigenous Youth

Abstract: Despite culturally appropriate content, the results of the review indicate that more controlled study designs using planned evaluations and valid outcome measures are needed in research on indigenous youth suicide prevention. Such changes may positively influence the future of research on indigenous youth suicide prevention as the outcomes and efficacy will be more reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 53 publications
2
50
0
1
Order By: Relevance
“…Based on evidence-based strategies which were identi ed from the review of systematic reviews and their combination with comments of experts of healthcare eld, 12 strategies were extracted, three of which had the highest score and effectiveness in suicide prevention: 1) case management and following up the attempters to prevent future attempts, 2) identi cation and treatment of depression, 3) improving registry for suicide and suicidal behavior. All of these strategies are consistent with systematic review and meta-analysis studies that are effective to reduce suicide in most societies [1,8,[12][13][14][15].…”
Section: Resultssupporting
confidence: 65%
“…Based on evidence-based strategies which were identi ed from the review of systematic reviews and their combination with comments of experts of healthcare eld, 12 strategies were extracted, three of which had the highest score and effectiveness in suicide prevention: 1) case management and following up the attempters to prevent future attempts, 2) identi cation and treatment of depression, 3) improving registry for suicide and suicidal behavior. All of these strategies are consistent with systematic review and meta-analysis studies that are effective to reduce suicide in most societies [1,8,[12][13][14][15].…”
Section: Resultssupporting
confidence: 65%
“…The percentage of participants in the evaluation who endorsed experiencing suicidal ideation within the past four weeks (24.8%) was also higher than the percentage of Australians aged between 12 and 17 who have "seriously considered" suicide within the past year (7.5%) (Lawrence et al, 2015). Similarly, 10.9% of participants in the evaluation reported ever making a suicide attempt, compared to 3.2% of young Australians who report this (Lawrence et al, 2015 Canada, 2013;New Zealand Government, 2016) and little is known about effective suicide prevention interventions for these populations (Clifford, Doran, & Tsey, 2013;Harlow, Bohanna, & Clough, 2014). Due to the small sample size we were not able to determine the impact of the safeTALK training on the Aboriginal and Torres Strait Islander participants in the present evaluation.…”
mentioning
confidence: 76%
“…Queensland's Indigenous youth (under 18) were recently found to die by suicide at a rate four times higher than their non-Indigenous counterparts (Commission for Children and Young People and Child Guardian, 2014), and this disparity widens to over 12 times for those under 14 years (Soole, Kolves, & De Leo, 2014). Several recent systematic reviews of Indigenous suicide prevention programs have recognised the absence of effective program evaluations to inform Indigenous suicide prevention policy and practice (Clifford, Doran, & Tsey, 2013;Harlow, Bohanna, & Clough, 2014;Ridani et al, 2015). The most recent overcoming Indigenous disadvantage (OID) report (Commonwealth of Australia, 2014) found that the incidence of psychological distress and that of self-harming in Aboriginal and Torres Strait Islander peoples had increased in the 3 years since the previous report.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Although research efforts have increasingly clarified these disparities, the evidence for effective prevention of Indigenous youth suicide remains noticeably lacking. Several recent systematic reviews of Indigenous suicide prevention programs have recognised the absence of effective program evaluations to inform Indigenous suicide prevention policy and practice (Clifford, Doran, & Tsey, 2013;Harlow, Bohanna, & Clough, 2014;Ridani et al, 2015). At the time of writing, no review of any intervention with evidence of a significant decrease in suicidal behaviours (either fatal behaviours or non-fatal behaviours such as suicide attempts, self-harm, or suicidal ideation) in Aboriginal or Torres Strait Islander young people had been published.…”
Section: What This Paper Addsmentioning
confidence: 99%